Продукційна система нечіткої логіки для оптимізації планів відновлювальної терапії - Ковалишин, Олег Степанович (Національний університет "Львівська політехніка", 2019)
Беручи до уваги необхідність узгодження індивідуальних планів реабілітації пацієнтів між собою, графіків роботи процедурних кабінетів, лікарів, та використання медичного обладнання, застосовано підхід до вирішення задачі багатокритеріальної оптимізації план-графіку роботи клініки, що складається з трьох основних етапів: побудова опорного план-графіку, що задовольняє жорстким обмеженням, оцінка якості план-графіку, послідовна оптимізація план-графіку з метою підвищення результатів оцінки. Для побудови опорного план-графіку розроблено універсальний незалежний від типу процедур метод, що забезпечує лінійну залежність часу вирішення відносно об’єму задачі. Для роботи методу визначено чинники, що впливають на пріоритетність включення процедур в план графік. Розроблено механізми аналізу реалістичності побудови план-графіку за умови наявності певних множин планів реабілітації, засоби вирішення конфліктних ситуацій при включенні процедур в план-графік, а також засоби послаблення певних жорстких вимог при неможливості його побудови. Реалізовано метод побудови план-графіків в режимі реального часу функціонування медичних установ, на основі використання нечіткої логіки, що забезпечило підвищення якості багатокритеріальної оптимізації в порівнянні з існуючими методами внаслідок перетворення векторного критерію в скалярну форму. Для здійснення багатокритеріальної оптимізації план-графіків відновлювальної терапії розроблено метод на основі генетичних алгоритмів, що зменшує вірогідність потрапляння розв’язків у локальні екстремуми. Диссертация посвящена решению важного научного задания – разработке эффективных методов автоматизированного построения план-графиков медицинских учреждений и их многокритериальной оптимизации с помощью элементов нечеткой логики и генетических алгоритмов. Принимая во внимание необходимость согласования индивидуальных планов реабилитации пациентов между собой, графиков работы процедурных кабинетов, врачей, и использования медицинского оборудования, применен подход к решению задачи многокритериальной оптимизации плана-графика работы клиники, который состоит из трех основных этапов: построение опорного плана-графика, что удовлетворяет жестким ограничением, оценка качества плана-графика, последовательная оптимизация плана-графика с целью повышения результатов оценки. Для построения опорного плана-графика разработан универсальный независимый от типа процедур метод, обеспечивающий линейную зависимость времени решения относительно объема задачи. Для работы метода определены факторы, влияющие на приоритетность включения процедур в план-график. Разработаны механизмы анализа реалистичности построения плана-графика при условии наличия определенных множеств планов реабилитации, средства решения конфликтных ситуаций при включении процедур в план-график, а также средства ослабления определенных жестких требований при невозможности его построения. Реализован метод построения план-графиков в режиме реального времени функционирования медицинских учреждений, на основе использования нечеткой логики, что обеспечило повышение качества многокритериальной оптимизации по сравнению с существующими методами результате преобразования векторного критерия в скалярную форму. Для осуществления многокритериальной оптимизации план-графиков восстановительной терапии разработан метод на основе генетических алгоритмов, что уменьшает вероятность попадания решений в локальные экстремумы. The thesis is devoted to the solution of an important scientific problem - development of effective methods of automated construction of medical institutions' timetables and their multicriteria optimization through the use of fuzzy logic elements and genetic algorithms. Work reveals functioning principles of the of rehabilitation and health recovery institutions, possibilities of increasing the efficiency of their work by constructing acceptable timetables, describes characteristics of individual programs of rehabilitation of patients. Taking into account the necessity of coordinating individual plans of rehabilitation of patients among themselves, schedules of work of procedural offices, doctors, and use of medical equipment, an approach to solving the problem of multicriteria optimization of the work timetable of the clinic, which consists of three main stages was applied: the construction of a reference timetable, which satisfies the strict constraints, the evaluation of the quality of the timetable, the consistent optimization of the schedule to improve the evaluation results. For the construction of the reference timetable, a universal independent from procedure types method was developed that provides a linear dependence of the decision time regarding the volume of the problem. It is based on the prioritization of the inclusion of procedures into the timetable and allows for the consideration of the requirements of an individual rehabilitation plan, the availability of the necessary qualified personnel for procedures, availability of medical equipment, etc. For the first time, a method for constructing schedules in real-time operation of medical institutions was developed, based on the use of fuzzy logic, which takes into account the wishes of patients in the conditions of hard and soft constraints of timetables of procedural offices of medical institutions, which allowed to abandon time-consuming a complete bustle of possible options. For this purpose, a fuzzy-logic controller based on the T-Controller system was developed, which made it possible to transform the linguistic data obtained by the collection of patient and medical personnel feedbacks into quantitative variables, to evaluate the quality of the clinic's work and to determine their level of satisfaction with the provided medical services. The optimization of regimens treatment schedules is performed without interruption from the environment of their conduction - medical institution, taking into account the requirements for the treatment process as hard constraints, which are determined by the rehabilitation plan and the provision of medical equipment and personnel, and soft restrictions, which depend on the wishes of patients. Methods for collecting and processing expert information have been improved, which is the basis for an integrated assessment of the quality of functioning of medical institutions. Based on expert surveys, a number of criteria have been established that influence schedules of work of medical institutions, taking into account the wishes of patients and medical staff during the construction of schedules. The software package, which uses the "thin client" architecture, was developed. This ensures independence from the hardware architecture of clients and their operating systems, the ease of adding a new feature, high security and high levels of bounce resistance. The proposed software package is the basis of information technology for automated construction and optimization of regenerative therapy schedules.
Продукционная система нечеткой логики для оптимизации планов восстановительной терапии
Production fuzzy logic system for medical rehabilitation plans optimization
Keywords: лікувальні заклади; план-графік; контролер нечіткої логіки; генетичні алгоритми; оптимізація планів відновлювальної терапії; програмний комплекс; лечебные учреждения; план-график; контролер нечеткой логики; генетические алгоритмы; оптимизация планов восстановительной терапии; программный комплекс; medical institutions; schedule; controller of fuzzy logic; genetic algorithms; optimization of plans of regenerative therapy; program complex; 004.89 + 004.932